Effects of Residual Dispersion on Intra-Channel Cross-Phase Modulation Induced Phase Fluctuation in Dispersion Managed Line - Nitu Syed; Tanjib Rubaiyat; Md Taosif Anowar (Institute of Advanced Engineering and Science, 2013)
The effects of residual dispersion on intra-channel cross-phase modulation (IXPM) induced phase perturbation in optical RZ pulse propagating in a periodically dispersion managed (DM) transmission line are investigated in this work. Using perturbed variational formulation, we have obtained several ordinary differential equations for various pulse parameters. These equations have been solved to identify phase perturbation in the DM cell of the system. Full numerical simulation of the nonlinear Schrodinger equation has been employed to identify effects of nonlinear phase fluctuation on pulse propagation and to investigate the intra-pulse interaction. The analytical result is verified by numerical simulation based on split-step Fourier method (SSFM). We therefore explore the effects of various parameters such as transmission distance, input power, duty cycle, and bit-rate on phase fluctuation for different single channel transmission models. Simulation results confirm significant improvement in the phase fluctuations due to IXPM by using dispersion managed line having some residual dispersion compared to perfect dispersion compensation. The outcome of our work is to explore the performance of the DM system with respect to some residual dispersion so that the IXPM induced phase fluctuations remain low.DOI:http://dx.doi.org/10.11591/ijece.v3i3.2526